Partners' internal stress and well‐being The role of dyadic coping and problem resolution - Donato Silvia (PERSONAL RELATIONSHIPS, 2023)
Couples' experiences of daily stress can be detrimental for partners' individual and relational well-being, specifically their identity as a couple, their relational satisfaction, and their life satisfaction. Grounded in the Systemic Transactional Model, this study aimed at analyzing factors that may safeguard partners and their relationship from detrimental effects of internal stress (i.e., stress that originates inside the relationship). We examined the buffering effect of partners' positive dyadic coping and internal problem resolution. Daily diary data were collected across 7 days from 82 heterosexual couples. Multilevel dyadic analyses showed that internal stress was negatively associated with partners' individual and relational well-being. Positive dyadic coping moderated the association between partners' internal stress and couple satisfaction for both partners, but not life satisfaction and couple identity. Moreover, for partners who reported a resolution to the internal problem, the negative associations of internal stress with life satisfaction, couple satisfaction, and couple identity were significantly lower than for those who did not resolve the internal problem. This study confirms the negative role of internal stress on well-being, shows the associations between internal stress and couple identity, and highlights the protective role of dyadic coping and internal problem resolution in couples' daily lives.